ANALISIS METODE FUZZY ANALYTIC HIERARCHY PROCESS (FAHP) DALAM MENENTUKAN POSISI JABATAN - Marischa Elveny; Rahmad Syah (Teknik Informatika Universitas Malikussaleh, 2014)
This study aims to determine positions with many criteria . In determining positions often appear the probability of every possible improper, because of the many factors that influence the assessment of existing options . In the Analytical Hierarchy Process (AHP) obtained uncertainty assessment is too subjective for qualitative data. Problems in determining the positions can be solved by Fuzzy Analytic Hierarchy Process (FAHP ), which uses valuation in the interval , so that qualitative data can provide a more objective assessment. The criteria used in this study is obedience, performance, responsibility, honesty, cooperation and leadership with three alternatives A, B and C. Based on this research can be concluded, performance becomes the highest criterion weighs 6.95 priority, then the priority weight 6.76 obedience, responsibility weighs 6.63 priority , honesty with weights 6.27 priorities , cooperation with priority weight 6.12 and the latter 's leadership with priority weights 6.2 . While the preferred alternative, Alternative C to get the highest score with 21.65 weight which is an alternative to the two weights B with 21.44 and the last alternative A 20.25 by weight